(untitled) (Research, Society and Development, 2022)
Objective: Identify and evaluate the scientific evidence for the use of acupuncture for pain relief in pediatric cancer patients. Method: This is an Integrative Review of the literature. This study’s search was performed in four relevant databases in health studies field: Medline, Embase, Lilacs and Cinahl. Results: Eighty-two publications were identified in the search. Ten were pre-selected and five were included in the revision. Favorable results showed pain relief in children and teenagers pediatric cancer patients outstand. Final considerations: Despite the small number of articles found, all of them showed the benefits of acupuncture for pain relief. It is important that acupuncturists turn themselves to research with better designs, so this complementary therapy, through evidence-based practices, can be used as another way of care and contribute to a better quality of life of these clients.